Enhancing EFL Writing Proficiency through Peer Feedback: A Mixed-Method Analysis - Ahmad, Farhan; Sultan, Salma; Rehman, Aiman; Al Dawood, Jaafar; Wardha , Wahaj Unnisa; Musa Elhassan, Musa Ahmed (Journal of Education Culture and Society, 2025)
Aim. This research attempts to examine the use of peer feedback to enhance writing skills and reveal the changes in students' performance and attitudes before and after the tests. In the EFL context, writing is crucial to becoming proficient in syntax, grammar, and vocabulary as it assists learners in expressing their thoughts concisely and critically.Method. Peer feedback plays a pivotal role in developing writing skills among EFL learners by presuming multiple viewpoints, promoting collaborative learning and presenting opportunities for constructive evaluation, which mutually results in enhanced proficiency in writing. Following Vygotsky's Sociocultural Theory (1978) as a framework, 40 students were selected randomly from undergraduates and analysed using a mixed-method approach.Results. The results reveal that peer feedback enhances the content of writing. Besides improving critical reading and thinking skills, it enables students to acknowledge their strengths and weaknesses in their writing. The research also encourages language learners to write regularly and precisely.Conclusion. This study can be helpful to bridge the gap between the learner and the instructor. It enhances our learning process and enables us to motivate and engage in the writing process. The research concludes that peer feedback is an integral component of effective language learning and offers solutions to reduce errors in writing. This research recommends that other researchers compare peer and teacher reviews to clarify which feedback is most suitable for students to improve their writing skills.